Complementary Feeding Practices and Weaning Practices in Morocco: A Systematic Review and Meta-Analysis - El Mossaoui, Mohamed; Barkat, Amina (International Journal of Child Health and Nutrition, 2024)
Introduction: Complementary feeding represents a crucial phase in an infant's developmental journey. Inadequate implementation, marked by an imbalance in both quantity and quality, can lead to varying degrees of nutritional disorders, whether from excess or deficiency. Study Objectives and Methods: Conducted from December 2023 to February 2024, this research aims to assess the weaning age and the age of initiating dietary diversification among Moroccan infants. Additionally, it seeks to scrutinize specific nutritional practices and behaviors within the Moroccan infant population. Our methodology involved an extensive bibliographic search using databases such as PubMed, Science Direct, Scopus, and Google Scholar, focusing on research conducted in Morocco from 2005 to 2020. Variables examined include the prevalence of breastfeeding at six months, the age of weaning, the commencement of dietary diversification at six months, and the prevalence of advice from healthcare professionals, particularly nursing experts, provided to Moroccan mothers. Results and Discussion: Complementary feeding practices in Morocco navigate the intersection of maternal nutritional beliefs and a plethora of infant feeding concepts, resulting in a complex landscape. The crucial role of medical and nursing personnel in conveying appropriate information and advice to Moroccan mothers is highlighted. Conclusion: Complementary feeding is a pivotal milestone in infant nutrition, necessitating adjustments and updates in Moroccan practices. The active involvement of medical and nursing personnel is essential to ensure optimal weight development and prevent infant nutritional disorders. Impact and Contribution of Patient or Public: Emphasizing the importance of the results in positively influencing infant feeding practices in Morocco, with a focus on the crucial role played by medical and nursing personnel in promoting infant health.